Recent Referees (Journal of Political Economy, 2020)
Previous articleNext article FreeRecent RefereesFull TextPDF Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Brant AbbottEliot AbramsRodrigo AdaoDavid AgrawalHeitor AlmeidaIsaiah AndrewsPeter ArcidiaconoDavid AtkinPierre AzoulayMichael BarnettMatthew BaronMarco BassettoChristiane BaumeisterChristian BayerDaniel BenjaminAlessandro BonattiStephane BonhommeTimo BoppartJordi BrandtsPeter BuisseretLuigi ButeraJuan CarrilloGabriel CarrollYuyu ChenLaurens CherchyeGabe Chodorow-ReichKaren ClayPhilip CookKerem CosarAnna CostelloNatalie CoxZoe CullenJakša CvitanićJoel DavidGiacomo De GiorgiFrancesca De NicolaGustavo De SouzaDaniela Del BocaBanu DemirEllora DerenoncourtManasi DeshpandeSebastian Di TellaAnna Dreber AlmenbergPierre DuboisPhilipp EisenhauerKfir EliazRobert EvansKirill EvdokimovHanming FangJames FeigenbaumShuaizhang FengJoseph FerrieTeresa FortAlexander FrankelGuillaume FrechetteChao FuAlberto GalassoDouglas GaleGeorge GeorgiadisAlbrecht GlitzBart GolsteynPhilip GravesDaniel GreenwaldYingni GuoMartin HackmannMarina HalacWilliam HanlonGlenn HarrisonJoop HartogOri HeffetzBart HobijnPär HolmbergRichard HornbeckDaniel HungermanErik HurstB. Kelsey JackTerrance JalbertPriit JeenasLoukas KarabarbounisFatih KarahanNeeraj KaushalNicolas KleinNarayana KocherlakotaNenad KosFrancis KramarzDavid LagakosKurt LavettiArthur LewbelAttila LindnerJason LindoChen LiuQingmin LiuKatrine LokenJens LudwigYao LuoMatthew MastenRaymond Mataloni, Jr.Filip MatejkaArnaud MaurelSteven MelloKonrad MenzelKarel MertensVirgiliu MidriganJosepa (Pepita) Miquel-FlorensaJoel MokyrJack MountjoyXiaosheng MuDaniel MurphyKyle MyersDavid NeumarkPaul NiehausPeter NormanRyan OpreaLuca OpromollaMarco OttavianiPablo OttonelloElias PapaioannouMathieu ParentiYoungmin ParkGert PeersmanHarry PeiKrishna PendakurSantiago PerezVincent PonsRichard PrisinzanoVincenzo QuadriniHeikki RantakariRonny RazinMichael RiordanWilliam RogersonDan-Olof RoothJesse RothsteinSutanuka RoyCian RuaneJuan Rubio-RamirezRaffaele SaggioTobias SalzMichael SattingerFlorian ScheuerJoshua SchwartzsteinCarmit SegalBradley ShapiroYotam Shem-TovItai SherClemens SialmHolger SiegAloysius SiowAndrzej SkrzypaczAlex SmolinMikkel SølvstenIsaac SorkinJörg SpenkuchFrancesco SquintaniJenna StearnsLudwig StraubDavid StrombergBruno StruloviciShinsuke TanakaJean TiroleGeorge TolleyTrevor TombeFabrice TourrePravin TrivediNick TsivanidisHelene TuronJohn Van ReenenFrederic VermeulenEwout VerriestSimon WeberMatthew WeinbergThomas WinberryAbigail WozniakKai Hao YangJunjian YiWes YinBasit ZafarYves ZenouOwen ZidarSeth ZimmermanUlf Zoelitz Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 128, Number 9September 2020 Article DOIhttps://doi.org/10.1086/711484 Views: 187 © 2020 by The University of Chicago. All rights reserved. Crossref reports no articles citing this article.